A gestão de vendas pessoais no varejo omnichannel: o caso da Livraria Cultura - Fernandes, Renato Braga (2018)
Research on multichannel retail management was focused on the growth of online channels and how it affected the company and consumers using traditional channels. With the maturation of e-commerce and the addition of portable channels, the retail environment faced a disruptive change. Compared to the multi-channel retail phase, Omnichannel Retail manages a much higher volume of channels. However, its biggest challenge is managing the experience of a new type of consumer. In Omnichannel Retail, the channels are interchangeable, inseparable, and used simultaneously throughout the purchase process. Acting in a business environment where the consumer is more informed and connected due to portable devices challenges retailers to qualify their personal sales management, making their offer more coherent and attractive. To do so, companies will need to perform a series of internal and external adaptations in their business model. This study had its starting point in finding out how a retail company should adapt its personal sales and sales management model to work in Omnichannel Retail, and found in the bookstore industry the case of Livraria Cultura. The company was chosen due to its relevance when compared to other national bookstores, and its history of acting in several channels, especially the sales channel, which always privileged the experience in physical stores. After data collection and analysis, evidences were found and linked in a way that allowed the establishment of seven theoretical propositions and a logical model of Livraria Cultura, which shows the challenges of personal sales management in an Omnichannel Retail